2014
DOI: 10.1155/2014/724274
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Differentially Expressed Genes and Signaling Pathways Related to Intramuscular Fat Deposition in Skeletal Muscle of Sex-Linked Dwarf Chickens

Abstract: Intramuscular fat (IMF) plays an important role in meat quality. However, the molecular mechanisms underlying IMF deposition in skeletal muscle have not been addressed for the sex-linked dwarf (SLD) chicken. In this study, potential candidate genes and signaling pathways related to IMF deposition in chicken leg muscle tissue were characterized using gene expression profiling of both 7-week-old SLD and normal chickens. A total of 173 differentially expressed genes (DEGs) were identified between the two breeds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…In this study, XLOC_064871 can trans-regulate TRIB3, indicating that XLOC_064871 might also play a vital role in adipocyte differentiation and fatty acid metabolism in pig. NR1D2 was highly expressed in skeletal muscle of Bantam chicken with high intramuscular fat content, and can induce the expression of PPARs, CEBPα and FABP4 genes, promoting adipogenic differentiation and affecting intramuscular fat deposition [74]. In this study, the expression of NR1D2 in intramuscular adipose tissue of LW pig was high, which was consistent with previous study.…”
Section: Pigssupporting
confidence: 91%
“…In this study, XLOC_064871 can trans-regulate TRIB3, indicating that XLOC_064871 might also play a vital role in adipocyte differentiation and fatty acid metabolism in pig. NR1D2 was highly expressed in skeletal muscle of Bantam chicken with high intramuscular fat content, and can induce the expression of PPARs, CEBPα and FABP4 genes, promoting adipogenic differentiation and affecting intramuscular fat deposition [74]. In this study, the expression of NR1D2 in intramuscular adipose tissue of LW pig was high, which was consistent with previous study.…”
Section: Pigssupporting
confidence: 91%
“…Next-generation sequencing has facilitated the research on the regulation of IMF deposition in chicken [ 24 ], cattle [ 25 ], and pigs [ 26 ]. Despite the characterization of the complete transcriptome of the goat mammary gland [ 27 ] and skin [ 28 ], to date, no information is available on the transcriptome for goat muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that the selection against abdominal fat resulted in a higher IMFC. The IMFC is an indicator of meat quality in animals, which is related with sensory satisfaction, meat flavour, tenderness and juiciness (Eikelenboom et al 1996;Fernandez et al 1999;Gerbens et al 2001;Suzuki et al 2005;Ye et al 2014).…”
Section: Selection Against Abdominal Fat Resulted In Higher Imfcmentioning
confidence: 99%
“…; Ye et al . ). Together with the result that there was a significant negative genetic correlation between IMFC and AFC, and the differences in IMFC grew from G8 on, these results indicated that they were attending the selection for lean line.…”
Section: Discussionmentioning
confidence: 97%